Analysis of running stability during 5000 m running*. Issue 4 (21st April 2019) - Hoenig, Tim; Hamacher, Daniel; Braumann, Klaus-Michael; Zech, Astrid; Hollander, Karsten
Abstract: In the analysis of human walking, the assessment of local dynamic stability (LDS) has been widely used to determine gait stability. To extend the concepts of LDS to the analysis of running biomechanics, this study aimed to compare LDS during exhaustive running between competitive and recreational runners. Fifteen recreational and fifteen competitive runners performed an exhaustive 5000 m run. Inertial measurement units at foot, pelvis, and thorax were used to determine local dynamic running stability as quantified by the largest Lyapunov exponent. In addition, we measured running velocity, lactate levels, perceived exertion, and foot strike patterns. LDS at the start, mid, and end of a 5000 m run was compared between the two groups by a two-way repeated-measures analysis of variance (ANOVA). Local dynamic stability increased during the run (thorax, pelvis) in both recreational and competitive runners ( P Thorax = 0.006; P Pelvis = 0.001). During the whole run, competitive runners showed a significantly higher LDS ( P = 0.029) compared to recreational runners at the foot kinematics. In conclusion, exhaustive running can lead to improvements in LDS, indicating a higher local dynamic stability of the running technique with increasing exhaustion. Furthermore, LDS of the foot differs between the two groups at all measurement points. The results of this study show the value of determining LDS in athletes as it can give a better understanding into the biomechanics of running.